2022
DOI: 10.3390/su141710712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental, Social, and Governance Performance on Corporate Financialization: Evidence from China

Abstract: Many nonfinancial firms in China invest increasingly in financial assets. To understand the driving factors behind this phenomenon, this paper examines the effect of environmental, social, and governance (ESG) performance on corporate financialization. The empirical results show that ESG performance has a positive effect on corporate financialization, suggesting that ESG activities are a tool for firms to seek financial arbitrage. Further examination confirms that corporate financialization of Chinese nonfinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…This decision implies that corporate governance practices have a statistically significant moderating effect on the influence of strategy implementation on the performance of road projects by Kenya Rural Roads Authority. The findings are in agreement with those in a study by Wang and Othman (2021) corporate governance significantly improves the effectiveness of road projects.…”
Section: Hypothesis Testingsupporting
confidence: 92%
See 1 more Smart Citation
“…This decision implies that corporate governance practices have a statistically significant moderating effect on the influence of strategy implementation on the performance of road projects by Kenya Rural Roads Authority. The findings are in agreement with those in a study by Wang and Othman (2021) corporate governance significantly improves the effectiveness of road projects.…”
Section: Hypothesis Testingsupporting
confidence: 92%
“…Furthermore, the literature review provided insights into the influence of Corporate Governance Practices on project success, which is corroborated by our findings. Wang and Othman (2021) demonstrated that corporate governance significantly improves the effectiveness of road projects in both Malaysia and China, emphasizing the role of transparency, accountability, and stakeholder engagement. Our study aligns with these findings, as we observed a significant positive correlation between Corporate Governance Practices and the performance of road projects in Kenya.…”
Section: Descriptive Statistics For Completion Timementioning
confidence: 99%
“…The phenomenon of financialization in enterprises is influenced by various factors, including macroeconomics [ 23 ], capital markets [ 24 ], and enterprise behaviors [ 25 ]. According to Deng, Zhang and Tang [ 26 ], firms may passively invest in financial assets as a survival strategy during economic shocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the existence of the delegation of authority from principle to agent, it means that the agent has the power and control of a company in its survival, therefore the agent is required to be always transparent in its management activities over a company. (Zhang et al, 2022). According to the agency theory, there is a conflict of interest between the financial owners of a company, including the accounting conservatism.…”
Section: Literature Review Theory Of Agency (Agency Theory)mentioning
confidence: 99%